2013
DOI: 10.1016/j.ijsu.2013.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Factors that can make an impact on decision-making and decision implementation in cancer multidisciplinary teams: An interview study of the provider perspective

Abstract: There is an increasing drive to improve the clinical role of the MDT within cancer care. This study demonstrates the main barriers that MDTs face in deciding on and, importantly, implementing a management plan. Further research should prospectively evaluate interventions to enhance translation of MDT decision-making into cancer care and thus to expedite and improve care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 38 publications
6
139
0
3
Order By: Relevance
“…[7–8] Moreover, multidisciplinary team (MDT) members highlighted the importance of having a complete patient profile, as well as all participating disciplines in attendance, for effective decision-making. [9] Improving MDT working therefore is complex although highly important with the cancer incidence and costs of care being predicted to rise, [10–11] whereas the significant financial pressures on the healthcare remain. [12] …”
Section: Introductionmentioning
confidence: 99%
“…[7–8] Moreover, multidisciplinary team (MDT) members highlighted the importance of having a complete patient profile, as well as all participating disciplines in attendance, for effective decision-making. [9] Improving MDT working therefore is complex although highly important with the cancer incidence and costs of care being predicted to rise, [10–11] whereas the significant financial pressures on the healthcare remain. [12] …”
Section: Introductionmentioning
confidence: 99%
“…The members considered the most important factors for effective MDT working to be those shown in table 2. A qualitative study of urological and gastrointestinal MDT members supports these findings citing nonattendance of key members at meetings, inadequate clinical information and technological failures as barriers to clinical decision making [54].…”
Section: Barriers To Effective Mdt Workingmentioning
confidence: 84%
“…Retrospective analyses have found that between 4% and 16% of MDT treatment plans were not actually implemented [11,53], and this may cause delays because of the need to refer to a different specialist [42]. The reasons that MDT recommendations were not implemented were usually patient choice or deterioration in fitness [11,53,54]; however, it is possible that last-minute cancellations of procedures or clinic appointments may affect the services available for other patients.…”
Section: Potential Problems With Mdt Managementmentioning
confidence: 99%
“…The respective experts were also viewed as core members of the IBD MDT (figure 2). Non-attendance of key members is a barrier to effective decision-making in the IBD MDT setting 24 25. Recommendations made by the participants to ensure attendance included making the IBD MDT part of the job plan and ensuring that it is protected time.…”
Section: Discussionmentioning
confidence: 99%